Characterization of a Unique γδ T-Cell Subset as a Specific Marker of Cytomegalovirus Infection Severity. (5th July 2020) - Kaminski, Hannah; Ménard, Coline; El Hayani, Bouchra; Adjibabi, And-Nan; Marsères, Gabriel; Courant, Maxime; Zouine, Atika; Pitard, Vincent; Garrigue, Isabelle; Burrel, Sonia; Moreau, Jean-François; Couzi, Lionel; et al.
Abstract: Cytomegalovirus (CMV) is a major infectious cause of death and disease after transplantation. We have previously demonstrated that the tissue-associated adaptive Vδ2 neg γδ T cells are key effectors responding to CMV and associated with recovery, contrasting with their innatelike circulating counterparts, the Vγ9 pos Vδ2 pos T cells that respond to phosphoantigens but not to CMV. A third Vγ9 neg Vδ2 pos subgroup with adaptive functions has been described in adults. In the current study, we demonstrate that these Vγ9 neg Vδ2 pos T cells are also components of the CMV immune response while presenting with distinct characteristics from Vδ2 neg γδ T cells. In a cohort of kidney transplant recipients, CMV seropositivity was the unique clinical parameter associated with Vγ9 neg Vδ2 pos T-cell expansion and differentiation. Extensive phenotyping demonstrated their substantial cytotoxic potential and activation during acute CMV primary infection or reinfection. In vitro, Vγ9 neg Vδ2 pos T cells responded specifically to CMV-infected cells in a T-cell receptor–dependent manner and through strong interferon γ production. Finally, Vγ9 neg Vδ2 pos T cells were the only γδ T-cell subset in which expansion was tightly correlated with the severity of CMV disease. To conclude, our results identify a new player in the immune response against CMV and open interesting clinical perspectives for using Vγ9 neg Vδ2 pos T cells as an immune marker for CMV disease severity in immunocompromised patients. Abstract : A newly described component of the immune response against cytomegalovirus (CMV), Vγ9 neg Vδ2 pos T cells show direct, specific, and T-cell receptor–dependent recognition of CMV-infected cells and are the only γδ T-cell subset with expansion tightly correlated with CMV disease severity.